Studies of modern pollen assemblages for pollen dispersal- deposition- preservation process understanding and for pollen-based reconstructions of past vegetation, climate, and human impact: A review based on case studies in China. (1st October 2016) - Xu, Qinghai; Zhang, Shengrui; Gaillard, Marie-jose; Li, Manyue; Cao, Xianyong; Tian, Fang; Li, Furong
Abstract: Fossil pollen, as a direct proxy record of past vegetation, and indirect proxy record of past climate, plays an essential role in revealing and reconstructing past vegetation and climate. However, relationships between pollen, vegetation and climate are not linear, hence quantitative reconstructions of past vegetation and climate based on pollen records are not straightforward, and results may be highly contradictory and difficult to interpret. One of the main causes of discrepancies between results has been the lack of comprehensive and systematical studies on modern pollen dispersal and deposition processes, particularly on the quantification of these processes. Based on empirical studies performed in China over the last 30 years, this paper provides the state-of-the-art of the understanding of pollen dispersal and deposition processes in China and the remaining questions to be investigated. We show that major progress has been achieved in the study of modern pollen dispersal and deposition processes, and in the application of models of the pollen-vegetation-climate relationships for quantitative reconstruction of past vegetation and climate. However, several issues are not entirely solved or understood yet, such as how to quantify the reworking and re-deposition of pollen grains in quaternary alluvial sediments, the influence of pollen preservation on pollen assemblages, and human impact on vegetation. Even so, the progress made during the last decades makes it possible to achieve significantly more precise and informative reconstructions of past vegetation, land-use and climate in China than was possible earlier. Highlights: First comprehensive review on Chinese studies of modern pollen assemblages. First review of case studies in China highlighting processes involved in pollen dispersal, deposition and preservation. First evaluation of the relationships of modern pollen, vegetation, land use, and climate in China and their applications. First test of the application of the REVEALS model to pollen-based reconstruction of past vegetation cover in China.